2020
DOI: 10.22257/kjp.2020.6.39.2.283
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Social Rejection on the Relationship between Narcissistic Vulnerability and Depression

Abstract: This study examined the moderating effect of social rejection on the relationship between vulnerability, which is one of the characteristics of pathological narcissism, and depression. Before the main experiment, five preliminary studies were conducted to make a new experimental paradigm, 'first impression effect study with video', to manipulate social rejection and non-rejection. In the main experiment, 152 participants from a university answered a questionnaire about narcissistic vulnerability and were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It demonstrated that narcissistic vulnerability had the greatest infuence on workplace bullying (victim aspect) among nurses. People with more severe narcissistic vulnerability may experience more negative emotions, such as depression, owing to their unrealistic expectations; thus, they demand only positive responses from others [17] and may also feel ashamed for seeking recognition from others [50]. A previous study on the efects of personality factors on workplace bullying among nurses reported that narcissistic vulnerability was signifcantly positively correlated with depression, anger, and negative emotions and negatively correlated with positive emotions [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It demonstrated that narcissistic vulnerability had the greatest infuence on workplace bullying (victim aspect) among nurses. People with more severe narcissistic vulnerability may experience more negative emotions, such as depression, owing to their unrealistic expectations; thus, they demand only positive responses from others [17] and may also feel ashamed for seeking recognition from others [50]. A previous study on the efects of personality factors on workplace bullying among nurses reported that narcissistic vulnerability was signifcantly positively correlated with depression, anger, and negative emotions and negatively correlated with positive emotions [41].…”
Section: Discussionmentioning
confidence: 99%
“…People with high perfectionistic self-presentation conceal their imperfections and tend to appear perfect to consequently receive and maintain a favorable reputation from others [26]. As people with severe perfectionistic self-presentation tend to avoid other peoples' negative evaluations of themselves and gracing their shortcomings [17,26], they are presumably more vulnerable to other peoples' negative evaluations or criticisms of their shortcomings that they may receive at work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation